Accuracy of Triage in Service in The Emergency Department (Literature Review) - Nur Soemah, Eka (Kirana Publisher (KNPub), 2023)
Service accuracy is the minimum standard of service that must be achieved by nurses in the emergency room, so that proper triage implementation is needed. Triage is the classification of patients based on the level of emergency by prioritising actions on airway (A), breathing (B), and circulation (C) disorders by considering facilities, human resources and the probability of patient life. The literature search in this literature review uses six databases with high and medium quality criteria, namely scient driect, IEEG, cedekia, Sci-hub, ProQuest, Pubmed. For previous studies using correlational analytics with a cross-sectional study approach, descriptive: combination (mixed methods) with sequential explanatory design. cross sectional. Check Prisma to guide this review. Titles, abstracts, full text and methodology were assessed for study eligibility. Data were tabulated and analysed narratively. Results: Nine journal literature met the inclusion criteria, with the major theme of triage accuracy in the Emergency Department. There were three journals analysing the accuracy of triage implementation, and four journals relating to triage accuracy. Factors that often appear in triage accuracy include nurses' understanding of triage, motivation and workload. Knowledge is one of the most important factors in the accuracy of triage implementation. Proper implementation of triage can reduce morbidity, disability, and mortality so as to improve service quality and customer satisfaction. Keywords: Accuracy of triage.